2(x+3)+x=4(-3)

Simple and best practice solution for 2(x+3)+x=4(-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)+x=4(-3) equation:


2(x+3)+x=4(-3)

We simplify the equation to the form, which is simple to understand
2(x+3)+x=4(-3)

Reorder the terms in parentheses
+(+2x+6)+x=4*(-3)

Remove unnecessary parentheses
+2x+6+x=+4+*(-3+)

Reorder the terms in parentheses
+2x+6+x=+(-12)

Remove unnecessary parentheses
+2x+6+x=-12

We move all terms containing x to the left and all other terms to the right.
+2x+1x=-12-6

We simplify left and right side of the equation.
+3x=-18

We divide both sides of the equation by 3 to get x.
x=-6

See similar equations:

| -5-r=10 | | f(x)=x^2+6x+18 | | 8x+3(2-3x)=25 | | 194-2x=43x+19 | | 24x^2+24x=0 | | 27+(4x-30)+(3x-10)+x=360 | | 4(1)-5y=9 | | a^3+7a^2+12a+24= | | 6x^2-9x-105=0 | | 15=200 | | -3x+4y=21 | | -10x+6y=-2(3-y) | | 65-131=11(x-1) | | x-11=-3-20 | | -2x=-6y+9 | | 11x-10x=8x+5 | | x+3=-28+10 | | 4a^2+2.25a+1=0 | | (x+8)(x)(x-2)=96 | | 3x/2+6x/5=5+x/5 | | 5z-z=5-37 | | x-42=48 | | 6v^2-9v-60=0 | | (x+4)(x)(x-2)=96 | | -20x=-10 | | 4x^2-24x+32= | | 2q+b=c | | 12-2x+3x-5-7x= | | 1x=5+0.75x | | 3.5x^7+4.5x^6-2.5x^2+4x=0 | | 42.75=4.75*x | | 75+0.10=400 |

Equations solver categories